PENGEMBANGAN SKALA SOCIAL DESIRABILITY - Ricky Oktapialdi; Medianta Tarigan; M. Ariez Musthofa (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This research aims to develop a social desirability scale in Indonesian. The method used is mixed method. Participant in the exploration stage amounted to 400 subjects. Whereas, in the second stage, which purposed to identify a psychometric properties (reliability and validity), participant amounted to 501 subjects. Data analysis in the first stage was open coding. For the second stage data analysis consisted of reliability estimation using Cronbach’s Alpha and test of construct validity using factorial validity with Confirmatory Factor Analysis (CFA) and convergent validity. The Result shows that the scale has a high reliability coefficient 0.76 alfa cronbach. Whereas, the test of model fit with CFA shows that the scale fits with the data with index of fit value of Comparative Fit Index (CFI) is 0.92, Goodness of Fit Index (GFI) is 0.93, Root Mean Square of Approximation (RMSEA) is 0.059, and Standardized Root Mean Residual (SRMR) is 0.052. A convergent validity also tested by correlating social desirability Indonesian scale with social desirability scale by Reynolds (1982).